Interest charges and the "said" ageing-related expenditures: A study of OECD countries - Aimé Philombe Zapji Ymélé (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2023)
Purpose: The main objective of this paper is to evaluate whether the interest charges on public debt could be a threat for the "said" ageing expenditures, This study attempts to analyze the effects of debt burdens known as interest charges in relation to the pensions and health care spending, The "said" ageing expenditures since the debate on this issue doesn't allow us to say that these expenses are totally linked to ageing. Design/methodology/approach: This study conducts an ordinary least squares analysis based on panel and cross-sectional data covering the period 2000-2020, The data are extracted from OECD statistic and from Eurostat statistic database, The research performs an analysis on 33 OECD countries, The dependents variables are pensions and health care spendings on GDP, The key independent variable is the interest charges, Other additional variables are included in the analysis that we can find in the text. Findings: The results of this study remain ambiguous and call for further study, Nevertheless, based on the current data, there is every reason to believe that, at present, expenditures on interest charges would not crowd out spending on pensions and health care, However, the significance of the demographic variables (old-age dependency ratio, total dependency ratio), and the increase in these ratios in the projections, point to a potential risk of collapse of the pension and health care systems. Research limitations/implications: The main difficulty encountered in this study was the collection of empirical literature dealing with our topic, Many papers used in our empirical literature was not always in relation with the topic of our research, Our challenge was to create the relation with those analyses to propose something original. Originality/value: We propose an innovative study, by proposing the analysis of debt charges in relation to pensions and health care expenditures, Several approaches in the same direction have used other parameters to analyze the costs of ageing, notably the debt to GDP ratio, We integrate other demographic variables such as the dependency ratio, macroeconomic indicators such as the savings rate, All these elements constitute the originality of our study.
Keywords: H51; H55; H63; J11; 330; Ageing; pensions; healthcare; interest charges